The effect of rapidly discharging psychiatric inpatients from Mental Health Act section during COVID-19: a cohort study. (25th June 2021) - Payne-Gill, J.; Whitfield, C.; Beck, A.
Abstract: Aims: In March 2020, the UK government ordered mental health services to free up bed space to help manage the COVID-19 pandemic. This meant service users detained under the Mental Health Act were discharged at a higher rate than normal. We analysed whether this decision compromised the safety of this vulnerable group of service users. Methods: We utilised a cohort study design and allocated service users to either the pre-rapid discharge, rapid discharge or post-rapid discharge group. We conducted a recurrent event analysis to assess group differences in the risk of experiencing negative outcomes during the 61 days post-discharge. We defined negative outcomes as crisis service use, re-admission to a psychiatric ward, community incidents of violence or self-harm and death by suicide. Results: The pre-rapid discharge cohort included 258 service users, the rapid discharge cohort 127 and the post-rapid discharge cohort 76. We found no statistical association between being in the rapid discharge cohort and the risk of experiencing negative outcomes (HR: 1.14, 95% CI: 0.72–1.8, p = 0.58) but a trend towards statistical significance for service users in the post-rapid discharge cohort (HR: 1.61, 95% CI: 0.91–2.83, p = 0.1). Conclusions: We did not find evidence that service users rapidly discharged from section experienced poorer outcomes. This raises the possibility that the Mental Health Act is applied in an overly restrictive manner, meaning that sections for some formally detained service users could be ended earlier without compromising safety.